BOK controls ER proteostasis and physiological ER stress responses in neurons - Walter, Franziska; D’Orsi, Beatrice; Jagannathan, Anagha; Dussmann, Heiko; Prehn, Jochen H. M. (Frontiers in Cell and Developmental Biology, 2022)
The Bcl-2 family proteins BAK and BAX control the crucial step of pore formation in the mitochondrial outer membrane during intrinsic apoptosis. Bcl-2-related ovarian killer (BOK) is a Bcl-2 family protein with high sequence similarity to BAK and BAX. However, intrinsic apoptosis can proceed in the absence of BOK. Unlike BAK and BAX, BOK is primarily located on the Endoplasmic Reticulum (ER) and Golgi membranes, suggesting a role for BOK in regulating ER homeostasis. In this study, we report that BOK is required for a full ER stress response. Employing previously characterized fluorescent protein-based ER stress reporter cell systems, we show that BOK deficient cells have an attenuated response to ER stress in all three signaling branches of the unfolded protein response. Fluo-4-based confocal Ca2+ imaging revealed that disruption of ER proteostasis in BOK-deficient cells was not linked to altered ER Ca2+ levels. Fluorescence recovery after photobleaching (FRAP) experiments using GRP78/BiP-eGFP demonstrated that GRP78 motility was significantly lower in BOK-deficient cells. This implied that less intra-luminal GRP78 was freely available and more of the ER chaperone bound to unfolded proteins. Collectively, these experiments suggest a new role for BOK in the protection of ER proteostasis and cellular responses to ER stress.